2017
DOI: 10.1039/c7fo00094d
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dietary sn-2 palmitic triacylglycerols in combination with docosahexaenoic acid or arachidonic acid on lipid metabolism and host faecal microbiota composition in Sprague Dawley rats

Abstract: Sn-2 palmitic acid triacylglycerols (sn2PA fat) and polyunsaturated fatty acids are thought to influence the metabolic status and intestinal bacterial population of the host. In this study, the impact of sn2PA fat in combination with DHA or ARA in the diet on lipid metabolism in the liver and faecal microbiota composition were investigated in rats fed diets containing sn2PA fat, 90% sn2PA fat + 10% DHA oil (wt%), or 90% sn2PA fat + 10% ARA oil (wt%). Tissue fatty acid composition was measured using gas chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
0
18
1
Order By: Relevance
“…Intake of long‐chain SFAs may increase lipid deposition, while MUFAs or PUFAs would inhibit lipid deposition . Such an effect could be dependent upon the fatty acid β‐oxidation, mRNA fatty acid synthase, and sterol regulatory element binding protein‐1c expression . Although the changes in body weight gain and feed intake, no significant difference was observed in inflammatory cytokines in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Intake of long‐chain SFAs may increase lipid deposition, while MUFAs or PUFAs would inhibit lipid deposition . Such an effect could be dependent upon the fatty acid β‐oxidation, mRNA fatty acid synthase, and sterol regulatory element binding protein‐1c expression . Although the changes in body weight gain and feed intake, no significant difference was observed in inflammatory cytokines in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Palmitoleic acid and conjugated linoleic acid may prevent fat deposition in the liver 26, 27 . Furthermore, intake of DHA and arachidonic acid (ARA) can significantly reduce hepatic weight, serum TAG and TC, epididymal fat as compared to palmitic acid, which would be associated with enhanced fatty acid β-oxidation, down-regulated mRNA fatty acid synthase and sterol regulatory element binding protein-1c expression 28 . And thus, intake of long-chain saturated fatty acids (the number of carbon skeletons greater than 12) may increase lipid deposition, while monounsaturated or polyunsaturated fatty acids would inhibit lipid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluated the effects of diets rich in palmitic acid supplemented with DHA or ALA oil on the microbiota of rats [ 109 ]. They observed that the diet with an addition of 10% ALA by weight was responsible for an increase in the content of Lactobacillus and Allobaculum , which are species responsible for improving intestinal health and promoting the production of SCFA.…”
Section: Inflammatory Process and Intestinal Microbiotamentioning
confidence: 99%
“…They observed that the diet with an addition of 10% ALA by weight was responsible for an increase in the content of Lactobacillus and Allobaculum , which are species responsible for improving intestinal health and promoting the production of SCFA. These SCFAs increased their concentrations by 41.9% when compared to the group that received only palmitic acid [ 109 ].…”
Section: Inflammatory Process and Intestinal Microbiotamentioning
confidence: 99%